Telmatocola sphagniphila gen. nov., sp. nov., a Novel Dendriform Planctomycete from Northern Wetlands - Kulichevskaya, Irina S.; Serkebaeva, Yulia M.; Kim, Yongkyu; Rijpstra, Irene C.; Sinninghe Damste, Jaap S.; Liesack, Werner; Dedysh, Svetlana N. (Frontiers in Microbiology, 2012)
Members of the phylum Planctomycetes are common inhabitants of northern wetlands. We used barcoded pyrosequencing to survey bacterial diversity in an acidic (pH 4.0) Sphagnum peat sampled from the peat bog Obukhovskoye, European North Russia. A total of 21189 bacterial 16S rRNA gene sequences were obtained, of which 1081 reads (5.1%) belonged to the Planctomycetes. Two-thirds of these sequences affiliated with planctomycete groups for which characterized representatives have not yet been available. Here, we describe two organisms from one of these previously uncultivated planctomycete groups. One isolate, strain OB3, was obtained from the peat sample used in our molecular study, while another strain, SP2T (=DSM 23888T = VKM B-2710T), was isolated from the peat bog Staroselskiy moss. Both isolates are represented by aerobic, budding, pink-pigmented, non-motile, spherical cells that are arranged in unusual, dendriform-like structures during growth on solid media. These bacteria are moderately acidophilic and mesophilic, capable of growth at pH 4.0-7.0 (optimum pH 5.0-5.5) and at 6-30ºC (optimum 20-26ºC). The preferred growth substrates are various heteropolysaccharides and sugars, the latter being utilized only if provided in low concentrations (≤ 0.025%). In contrast to other described planctomycetes, strains SP2T and OB3 possess weak cellulolytic potential. The major fatty acids are C16:1ω5c, C18:1ω5c, C16:0 and C18:0. Characteristic lipids are the n-C31 polyunsaturated alkene (9-10 double bonds) and C30:1/C32:1 (ω-1) hydroxy fatty acids. The G+C content of the DNA is 58.5-59.0 mol%. Strains SP2T and OB3 share identical 16S rRNA gene sequences, which exhibit only 86 and 87% similarity to those of Gemmata obscuriglobus and Zavarzinella formosa. Based on the characteristics reported here, we propose to classify these novel planctomycetes as representatives of a novel genus and species, Telmatocola sphagniphila gen. nov., sp. nov.